The effect of dissolved oxygen on common carp (Cyprinus carpio) and basil (Ocimum basilicum) in the aquaponics system - Homoki, Dávid; Odunayo, Toviho; Minya, Dániel; Kovács, László; Lelesz, Judit; Bársony, Péter; Fehér, Milán; Kövics, György; Stündl, László (Acta Agraria Debreceniensis, 2021)
Aquaponics is an integrated system that combines fish farming (aquaculture) and hydroponic plant production. The objective of this study was to examine how the level of dissolved oxygen with or without an air pump affects water quality, fish output and plant growth parameters for common carp (Cyprinus carpio) and basil (Ocimum basilicum). Ebb – and flood aquaponics systems (with automatic syphon) was used. Two treatments were set in this experiment, one of which was the aquaponics system without air pump (unit I), where water of the plant bed was pumped two directions, one falling back to the fish tank oxygenating the water the other was pumped to the hydroponics unit. The other system (unit II) was designed with an air pump.In the course of the study, water quality parameters, such as oxygen saturation, dissolved oxygen (DO), electrical conductivity (EC) and nitrite were significantly different (p0.05) between the treatments.